PENGELOLAAN TANAMAN TERPADU PADI VARIETAS UNGGUL BARU DI LAHAN SAWAH TADAH HUJAN DI KABUPEN JAYAPURA, PAPUA - Petrus A Beding; Batseba M. W. Tiro (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The cultivation technology and the use of new superior varieties (VUB) is one of the main components in increasing rice productivity in rainfed land. The study aims to evaluate the performance of the rice VUB in rainfed lowland cultivated land with integrated crop management (PTT) approach. This activity was carried out in the village of Benyom Jaya 1, Nimbokrang District, Jayapura Regency, Papua Province, from April to September 2017 using a Randomized Group Design. each variety used is. VUB tested by Inpari, 7, Inpari 30, Inpari 32 and Inpari 33, were planted in a plot measuring 2 hectares of experimental area for each treatment was 20 x 20 m2. The parameters evaluated include plant height, number of tillers, yield components and pest and disease attacks. The results of the study showed that the Inpari 33 variety gave a significantly different growth and yield to the Inpari 30 and 7 varieties. The suitable and high yielding varieties at the study site were the high production varieties obtained from the Inpari 33 variety (5.9 t / ha) and the lowest variety is Inpari 32 (4.47 t / ha) Keywords: Rice Varieties, Rainfed Rice Fields, Performance, PTT